Intranet - alternativa za realizacijo informacijskega sistema - Jaklič, Jurij (Uporabna informatika (Ljubljana), 1996)
A typical information system can be represented by three different views or layers: data structure layer, system structure layer, and system environment layer. In all three layers the development of new information technologies hasa great impact. The most disruptive new technologies are those developed for the global computer network Internet and the object oriented methodology. In this paper we define intranet as an alternative possibility for implementation of an information system and analyze its advantages and disandvantages.
Keywords: informacijske tehnologije; informacijski sistemi; intranet; strukturiranost podatkov